Răspuns :
[tex] 4^{x}-3* 2^{x}+2=0 [/tex]
[tex] (2^{x}) ^{2} -3* 2^{x} +2=0[/tex]
Notam [tex] 2^{x} [/tex] cu t si avem:
[tex] t^{2} -3t+2=0[/tex]
Δ=[tex] b^{2}-4ac[/tex] a=1 b=(-3) c=2
Δ=[tex] (-3)^{2} -4*2*1[/tex]
Δ=9-8
Δ=1 ⇒ [tex] t_{1}= \frac{-b+ \sqrt{delta} }{2a} [/tex]
[[tex] t_{1}= \frac{-(-3)+ \sqrt{1} }{2*1} [/tex]
[tex] t_{1}= \frac{3+1}{2} [/tex]
[tex] t_{1}= \frac{4}{2} [/tex]
[tex] t_{1}=2 [/tex]
[tex] t_{2}= \frac{-b- \sqrt{delta} }{2a} [/tex]
[tex] t_{2}= \frac{-(-3)- \sqrt{1} }{2*1} [/tex]
[tex] t_{2}= \frac{3-1}{2} [/tex]
[tex] t_{2}= \frac{2}{2} [/tex]
[tex] t_{2}=1[/tex]
[tex] t_{1}=2 [/tex] ⇒ [tex] 2^{x}=2[/tex] ⇒ x=1
[tex] t_{2} =1[/tex] ⇒ [tex] 2^{x}=1[/tex] ⇒ x=0
Deci solutiile sunt 0 si 1
[tex] (2^{x}) ^{2} -3* 2^{x} +2=0[/tex]
Notam [tex] 2^{x} [/tex] cu t si avem:
[tex] t^{2} -3t+2=0[/tex]
Δ=[tex] b^{2}-4ac[/tex] a=1 b=(-3) c=2
Δ=[tex] (-3)^{2} -4*2*1[/tex]
Δ=9-8
Δ=1 ⇒ [tex] t_{1}= \frac{-b+ \sqrt{delta} }{2a} [/tex]
[[tex] t_{1}= \frac{-(-3)+ \sqrt{1} }{2*1} [/tex]
[tex] t_{1}= \frac{3+1}{2} [/tex]
[tex] t_{1}= \frac{4}{2} [/tex]
[tex] t_{1}=2 [/tex]
[tex] t_{2}= \frac{-b- \sqrt{delta} }{2a} [/tex]
[tex] t_{2}= \frac{-(-3)- \sqrt{1} }{2*1} [/tex]
[tex] t_{2}= \frac{3-1}{2} [/tex]
[tex] t_{2}= \frac{2}{2} [/tex]
[tex] t_{2}=1[/tex]
[tex] t_{1}=2 [/tex] ⇒ [tex] 2^{x}=2[/tex] ⇒ x=1
[tex] t_{2} =1[/tex] ⇒ [tex] 2^{x}=1[/tex] ⇒ x=0
Deci solutiile sunt 0 si 1